2015
DOI: 10.1136/neurintsurg-2015-011834
|View full text |Cite
|
Sign up to set email alerts
|

National treatment practices in the management of infectious intracranial aneurysms and infective endocarditis

Abstract: In this NIS database study, the majority of patients with IIAs were managed non-operatively, regardless of rupture status. Further investigation is warranted to standardize the management of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 29 publications
0
50
1
Order By: Relevance
“…It is difficult to draw valid conclusions concerning the outcome of patients with ICMA, 184 for many reasons: (1) ICMA is a relatively rare condition, and there are no controlled studies. (2) Reviews of reported series often span decades during which radiologic modalities, interventional techniques, microvascular surgery, and management of underlying conditions evolved and improved over time.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to draw valid conclusions concerning the outcome of patients with ICMA, 184 for many reasons: (1) ICMA is a relatively rare condition, and there are no controlled studies. (2) Reviews of reported series often span decades during which radiologic modalities, interventional techniques, microvascular surgery, and management of underlying conditions evolved and improved over time.…”
Section: Prognosismentioning
confidence: 99%
“…Patients who have rupture of an ICMA have worse outcomes than those who do not. 112,117,125,135,162,184 Patients with multiple ICMAs have worse outcomes than those with a single ICMA. 135,174 Mortality was significantly higher for older people and for those with meningitis and ICMA located in the vertebrobasilar territory.…”
Section: Prognosismentioning
confidence: 99%
“…After screening of the titles and abstracts, 63 studies were selected for full review [1,3,4,7,10,11,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71]. Thirty studies with 2 or more patients and 33 case reports with a total number of 814 patients were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Patients who require valve surgery or other type of open heart surgery may be more critically ill and at higher morbidity and mortality risk as compared to those who may not need cardiac surgery, and this may account for the lack of studies including these patients. A recently published paper by Singla et al [12], performed using the Nationwide Inpatient Sample database on the national treatment practices in the management of infectious intracranial aneurysms and infective endocarditis, revealed that the majority of patients with infectious intracranial aneurysms were managed conservatively. In this cohort, 18.6% underwent endovascular embolization or surgical clipping of the aneurysm independently of the rupture status, with only 18% of ruptured aneurysms and 25% of unruptured aneurysms undergoing treatment to exclude the aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cardiac procedures were only performed in 18.6% of patients with ruptured aneurysms and 15.6% of those with unruptured aneurysms. Only 1.5% of patients had cardiac surgery and aneurysm treatment within the same admission [12]. …”
Section: Discussionmentioning
confidence: 99%